The Communication Discipline and Peace Education: A Valuable Intersection for Disrupting Violence in Communication Centers - Victoria McDermott; Cortney Smith; Amy R. May (Central States Communication Association, 2022)
Violence is a significant issue impacting the physical, mental, social, and economic health of our learning communities. For decades the discipline of peace education has explored the effects of nonphysical violence on students and educators, as well as ways to create more peaceful, less violent, and equitable educational practices. While communication frameworks have been used in peace education research, no research found has theorized the potential value of peace education for the communication discipline. Using the contextual background of communication centers, this piece seeks to disrupt steadfast norms and practices within communication centers from the perspective of peace education. We provide an overview of the field of peace education and explicate opportunities within the communication discipline to use peace education frameworks, theory, and practice to develop pedagogies of renewal and close with practical recommendations for communication centers going forward.